Factors Affecting Students’ Desire to Take Upcoming Online Courses after E-learning Experience During Covid 19 - Nguyen, Nga Thuy; Tran, Huong Thi Thu (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Since 2020, Covid 19 has completely changed the daily activities of almost all nations, and education has been heavily affected. Because of school closures, face-to-face classrooms were halted or replaced with online classes in which both lecturers and learners had to adjust their teaching and learning styles to cope with unexpected situations. The ‘new normal’ of learning from homes, spending hours staring at screens, and struggling with piles of online tasks has somehow demotivated students to continue learning. This study explores factors affecting students’ desire to take online courses after experiencing e-learning during Covid 19. Nine hundred fifty-five students of Vietnam National University took part in the survey via an online questionnaire. Data were analyzed using SPSS20; correlation, hierarchical regression was employed to examine how online factors influence students’ decision. The research results showed that skill enhancement, self-regulated learning, lecturer interaction during the course were among the most important predictors of students’ desire to take more online courses. In contrast, student interaction imposed no significant influence. This study gives the theoretical background for other studies in the same field and suggests practical implications for governments and universities to implement online training better to cope with the pandemic...